Cultivo do cogumelo comestível Pleurotus florida em ramas de mandioca - Graciolli, Luis Antônio [UNESP]; Caetano, Circélia Pereira dos Santos [UNESP]; Leonel, Magali [UNESP]; Aguiar, Eduardo Barreto [UNESP] (My University, 2010)
The aerial part of cassava, consisting of leaves and stems, supplemented with rice bran, soybean and wheat, at concentrations of 10 and 20% was used as substrate for the production of edible mushroom P. florida. The cultivation was carried out in glass bottles and inoculant multiplied on rice grains. After the complete colonization of the substrate, the flasks were transferred to a fructification shed, without control of temperature and average damp of 80-90%. The addition of bran in the substrate did not influence mycelium growth, productivity and biological efficiency of P. florida. The addition of soybean bran at a concentration of 20%, inhibited the growth of mushroom mycelium. The pure substrate was effective for the production of the mushroom P. florida, showed satisfactory values of productivity (210 g.kg-1) and biological efficiency (78.2%) and may be recommended as an alternative to the cultivation of this fungus.

A parte aérea da mandioca, composta por folhas e hastes, suplementada ou não com farelos de arroz, soja e trigo, nas concentrações de 10 e 20%, foi utilizada como substrato na produção do cogumelo comestível P. florida. O cultivo foi realizado em frascos de vidro e o inoculante multiplicado em arroz parboilizado. Após a completa colonização do substrato, os frascos foram transferidos para um barracão de frutificação, sem controle de temperatura e umidade relativa mantida entre 80-90%. A adição de farelos no substrato não influenciou o crescimento micelial, a produtividade e a eficiência biológica de P. florida. A adição de farelo de soja, na concentração de 20%, inibiu o crescimento micelial do cogumelo. O substrato rama de mandioca puro foi eficiente para a produção do cogumelo P. florida, apresentou valores satisfatórios de produtividade (210 g.kg-1 ) e eficiência biológica (78,2%), podendo ser recomendado como alternativa para o cultivo deste fungo.
Cultivation of edible mushroom Pleurotus florida on cassava foliage
Keywords: Mushroom; Pleurotus florida; Cassava stems; Biological efficiency; Agricultural wastes; Cogumelo; Pleurotus florida; Ramas de mandioca; Eficiência biológica; Resíduo agrícola